Gender specific differences of the ethanol and nicotine toxicity verified by the use of mathematical models - Tušek, Kristina (Array, 2019)
Beside the pandemic of obesity, the binge drinking becomes a huge problem. The toxicity of consuming alcohol and smoking in the late adolescent population was examined using mathematical models. The body was divided into compartments for two different models; (i) the ethanol model (4 compartments: central compartment, muscle and fat compartment, liver compartment and gastrointestinal compartment) and (ii) the nicotine model (2 compartments: liver compartment and central compartment). Different alcohol contents simulated consumptions of 90 mL of spirits; 900 mL of beer or 600 mL of wine. Nicotine metabolism simulation was performed for three different initial doses of nicotine (light, medium and strong cigarettes). Significant differences are observed regarding the gender; where the maximum ethanol concentration is reached at 0.5 h (males: 27 mmol/dm3 and females: 33 mmol/dm3) in the gastrointestinal compartment while complete nicotine degradation in the liver takes approximately 10 h and in the central compartment 15 h, respectively. The skewness and kurtosis of the toxin concentrations showed their relation with the symmetry of the toxin retention in the body. Results show preferable positively skewed distribution which implies a shorter retention time in the organism while higher kurtosis implies higher toxin concentration.